Quantitative analysis of regional trigeminal nerve microstructure in healthy young adults: a magnetic resonance imaging study - Arruda, Eduardo Rocha (2025)
The trigeminal nerve (TGN) has been extensively studied, mainly due to cases of classical neuralgia, whose main cause is neurovascular compression at its root. However, there is evidence that this compression is common in healthy individuals without symptoms of neuralgia. This evidence leads us to believe that establishing reference parameters for normal TGN in healthy individuals is important for future studies on trigeminal neuralgia (TN). Diffusion tensor imaging (DTI) is the magnetic resonance technique used par excellence for the quantitative in vivo study of axonal bundles in the central nervous system, assessing the integrity of axonal bundles in the white matter through diffusion metrics, with fractional anisotropy (FA) being the most widely used. Thus, the aim of this study was to evaluate the effect of sex and age on the values of diffusion metrics: FA, mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) and the absolute, relative volumes and asymmetry, in different regions of interest (ROIs) of the TGN: root entry zone (REZ), middle portion of the cisterna (cisterna) and Meckel\'s cave in healthy young adults, in order to establish parameters that serve as a reference of normality for the healthy trigeminal nerve. 300 T1-weighted and diffusion-weighted structural images of 150 healthy men and 150 women were obtained, both groups in the age ranges of 22-25, 26-30 and 31-35 years, from the Human Connectome Project - HCP database. Through these, the values of FA, MD, AD and RD, absolute, relative volumes and asymmetry of all diffusion metrics and volumes in the defined ROIs of the TGN bilaterally were calculated. The variability of diffusion metrics among ROIs was: FA (20%-27%), MD (20%-25%), AD (23%-30%) and RD (22%-25%). The REZ showed asymmetry prevalent on the right side, unlike the other ROIs, except FA, in which the root asymmetry was on the left. The effect of sex had no influence on the asymmetry values, but was marked on the absolute and relative volumes, with higher values among men. Age presented specific values in the diffusion metrics, asymmetry and volumes. Our analyses revealed evident regional differences among TGN, with distinct heterogeneities in the diffusion metrics and volumes. The asymmetries and variability of the diffusion metrics observed provide a good reference for normality standards for studies investigating TN. Sex has a significant impact on diffusion metrics and mainly on TGN volumes in men, reinforcing that the differences between men and women should be taken into account in studies on TGN. The effect of age was limited, not contributing significantly to our analyses.